Interprofessional practice in healthcare: Experiences of a faculty learning community. Issue 4 (3rd July 2016) - Robinson-Dooley, Vanessa; Nichols, Quienton
ABSTRACT: Healthcare reform has had its impact on many health professionals as well as clinical settings, particularly with the enactment of the Affordable Care Act. In healthcare settings, healthcare teams are challenged with new systems of care and changing philosophies of management. However, healthcare providers retain a distinctive sense that they cannot always provide care without some form of collaboration. This article presents the results of a pilot study, which measured the effectiveness of a model of practice utilised at a faculty-practitioner operated university community clinic. The purpose of the study was to measure the perceived effectiveness of a practice model, client satisfaction, and students' perceptions of learning. Implications of this pilot study include providing an interprofessional practice model, which can be replicated in any healthcare setting. This study also provides an opportunity to improve student learning in degree programmes where practice is a significant aspect of the learning process.